Food and Beverage Management / A Selection of Readings - Davis Bernard; Lockwood Andrew (Butterworth Heinemann, 1994)
The text provides specially selected material to further students' understanding of food and beverage operations. Preface, Introduction, Strategic Considerations, Reviewing the Performance of Corporate Food and Beverage, Branding Strategies for Food and Beverage Operations, The Application of Retailing to Food and Beverage Operations, Restaurant Company Financial Performance Analysis, Planning and Design, Location Analysis and Market Feasibility, Catering Systems, Design and Layout, Managing Operations, Managing Quality in Food and Beverage Operations, Marketing and Merchandising, Food and Beverage Purchasing, Controlling Operations, Monitoring Customer Satisfaction, Managing Profitability, Productivity Improvement, Food Hygiene and HACCP, Panel Questions, The View from the Industry, Index.